Binding of triazole-linked galactosyl arylsulfonamides to galectin-3 affects Trypanosoma cruzi cell invasion. Issue 21 (1st November 2017) - Marchiori, Marcelo Fiori; Riul, Thalita B.; Oliveira Bortot, Leandro; Andrade, Peterson; Junqueira, Getúlio G.; Foca, Giuseppina; Doti, Nunzianna; Ruvo, Menotti; Dias-Baruffi, Marcelo; Carvalho, Ivone; Campo, Vanessa Leiria
Graphical abstract: Abstract: The synthesis of the O-3 triazole-linked galactosyl arylsulfonamides1 –7 as potential inhibitors of Trypanosoma cruzi cell invasion is described. These target compounds were synthesized by Cu(I)-catalysed azide-alkyne cycloaddition reaction ('click chemistry') between different azide arylsulfonamides and the alkyne-based sugar 3-O-propynyl-βGalOMe. Inhibition assays of T. cruzi cell invasion with compounds1 –7 showed reduced values of infection index (∼20) for compounds3 and5, bearing the corresponding 5-methylisoxazole and 2, 4-dimethoxypyrimidine groups, which also presented higher binding affinities to galectin-3 (EC50 17–18 μM) in Corning Epic label-free assays. In agreement with experimental results, the assessment of the theoretical binding of compounds1 –7 to galectin-3 by MM/PBSA method displayed higher affinities for compounds3 (−9.7 kcal/mol) and5 (−11.1 kcal/mol). Overall, these achievements highlight compounds3 and5 as potential T. cruzi cell invasion blockers by means of a galectin-3 binding-related mechanism, revealing galectin-3 as an important host target for design of novel anti-trypanosomal agents.